Current Practice of Physical Therapists: An evidence-based practice survey - Naveed Arshad, Maryam Shabbir, Hafiz Muhammad Manan Haider Khan, Maryam Naeem, Azhar Ayyub, Muhammad Zeeshan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patient/client management is comprehensive multidirectional process. It includes patient client examination, evaluation, diagnosis, prognosis, intervention and then discharge plans from supervised treatment to follow ups. The process of examination includes comprehensive history taking, performing systemic review and special tests and measures. Aim: To investigate Pakistani physiotherapists’ current practice, skills and understanding of evidence-based practice in order to improve the utilization of the evidence base in physiotherapy in the country. Methods: This observational cross section study was done in Pakistan Institute of Medical Sciences and Islamabad Medical and Dental College, Islamabad between January 2021 and March 2021. Physiotherapists(n=369) were contacted through non-probability convenience sampling technique. Respondents were contacted at clinical facilities in the twin cities of Pakistan. The content of the questionnaire was validated using the literature and the method of Lynn MR et al. The results were extracted, conclusion was drawn, suggestions and recommendations were made. Results: The participants mean age was 27.58±7.41 years. The male/female ratio was almost same. Approximately half of the respondents 50.4% were agreed about the role of EBP in practice.57% respondents were agreed that EBP removes the art from clinical practice. 58.5% respondents were agreed about benefit of EBP and EBP improves clinical outcomes and 53.4%respondents were agreed about help of EBP in decision making. Attitude and knowledge need analysis was positive but there found compromise in utilization of this evidence-based practice, while this study showed more utilization. Conclusion: Five steps of evidence-based practice were found being infrequently practiced. Physiotherapists had good to fair understanding of evidence-based practice. Physiotherapists had fair to poor appraisal skills. Keywords: Clinician practice; Data base; Evidence-based practice; Physical therapist; Practice guideline; Patient management.